1981
DOI: 10.1055/s-0038-1650173
|View full text |Cite
|
Sign up to set email alerts
|

Studies in Man and Experimental Animals of a Low Molecular Weight Heparin Fraction

Abstract: SummaryIn vitro and in vivo studies were carried out on a commercially prepared low molecular weight heparin fraction. By APTT assay the fraction had a specific activity of half that of unfractionated mucosal heparin, yet retained full potency by anti-Xa assay (both clotting and chromogenic substrate). When administered intravenously to human volunteers, the anti-Xa/APTT ratio remained the same as it was in vitro. However, after subcutaneous injection, the ratio increased and anti-Xa activity could not be full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 7 publications
4
43
0
Order By: Relevance
“…In animal experiments, LH has proved as effective as UH in preventing thrombosis [6][7][8], Animal experiments have also suggested that the bleeding risk using LH is reduced compared to UH [7,8], Further more, LH seems less prone to induce platelet aggregation [9] and lipase activity [10]. Sub cutaneous administration of LH is effective in the prevention of DVT [11], but bleeding is still a potential hazard [12], Increased halflife and improved bioavailability [13,14] of LH as compared to UH suggest that LH is particularly suitable for subcutaneous ad ministration.…”
Section: Introductionmentioning
confidence: 99%
“…In animal experiments, LH has proved as effective as UH in preventing thrombosis [6][7][8], Animal experiments have also suggested that the bleeding risk using LH is reduced compared to UH [7,8], Further more, LH seems less prone to induce platelet aggregation [9] and lipase activity [10]. Sub cutaneous administration of LH is effective in the prevention of DVT [11], but bleeding is still a potential hazard [12], Increased halflife and improved bioavailability [13,14] of LH as compared to UH suggest that LH is particularly suitable for subcutaneous ad ministration.…”
Section: Introductionmentioning
confidence: 99%
“…Low-molecular-weight (LMW) heparins strongly inhibit factor Xa [12,15], but have relatively little activity either in anti-Ila as says or in tests of overall anticoagulant activ ity such as the activated partial thromboplas tin time. Nevertheless, they are effective anti thrombotic agents [11].…”
Section: Introductionmentioning
confidence: 99%
“…In animal models low concentrations of heparin have been shown to be highly effective in preventing stasis thrombosis. 28 This has now been amply confirmed by numerous clinical trials. The advent of LMWH, in terms of effectiveness, ease of use, and minimal risk, represents an important therapeutic advance in achieving effective prophylaxis throughout the period of maximum risk after major surgery.…”
Section: Whither Thromboprophylaxis After Total Hip Replacement? D Pmentioning
confidence: 83%